Adaptive Isolation and Zero-Trust Strategies for Secure Multi-Tenant Cloud Environments: An Integrated Framework - Dr. Elena Moretti (Academic Reseach Library for International Journal of Computer Science & Information System, 2025)
Background: Multi-tenant cloud computing offers transformative efficiency and scalability benefits by enabling multiple independent tenants to share common infrastructure. However, co-residency, resource contention, and management complexity introduce substantial security and isolation challenges (Odun-Ayo et al., 2017; Kyle Bai, 2019). Recent operational practices and orchestration tools such as OpenStack and Ansible interact with tenant isolation policies and quota controls, affecting both attack surfaces and defensive posture (Manage Block Storage service quotas, 2019; Margaret Rouse, 2019). Simultaneously, the zero-trust security paradigm has emerged as a structured approach to minimize implicit trust in cloud environments (Hariharan, 2025). Objective: This article presents an integrated theoretical and practical framework that synthesizes host-level aggregation controls, quota enforcement, orchestration-driven configuration, and zero-trust micro-policies to achieve adaptive, provable isolation in multi-tenant clouds. The framework is grounded in the selected literature and operational documentation provided by the references. Methods: We adopt a mixed-style methodological narrative, coupling normative systems analysis of OpenStack management primitives and orchestration workflows with conceptual modeling of zero-trust controls. The article develops modular policy constructs, threat scenario mappings, and formalizes isolation goals descriptively, then subjects the framework to a descriptive, comparative analysis against documented multi- tenancy issues and operational guidance (MANAGE HOST AGGREGATES, 2019; Kyle Bai, 2019; Odun-Ayo et al., 2017). Results: The integrated framework demonstrates how explicit management of host aggregates, disciplined block-storage quota policies, and automated configuration via playbook paradigms produce measurable reductions in shared-resource exposure vectors. The zero-trust overlay further constrains lateral movement and privileges, reducing risk from tenant compromise while preserving elastic provisioning. We detail operational steps, governance controls, and an extensible policy taxonomy. Conclusions: By combining infrastructure management primitives with automated orchestration and zero-trust micro-policies, cloud providers and tenants can achieve stronger, adaptable isolation without fundamentally compromising multi-tenant economics. Implementation requires coordinated governance, continuous validation, and enhancements to existing orchestration ecosystems. Future work should empirically validate the framework across varied deployments and extend it to incorporate emerging runtime-level attestation techniques.